2009
DOI: 10.1038/jhh.2009.38
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of blood-pressure-lowering effect following a missed dose of aliskiren, irbesartan or ramipril: results of a randomized, double-blind study

Abstract: Most patients inadvertently miss an occasional dose of antihypertensive therapy, and hence drugs that provide sustained blood-pressure (BP) reduction beyond the 24-h dosing interval are desirable. The primary objective of this study was to compare the 24-h mean ambulatory BP reductions from baseline after a simulated missed dose of the direct renin inhibitor aliskiren, irbesartan or ramipril. In this double-blind study, 654 hypertensive patients (24-h mean ambulatory diastolic BP (MADBP) X85 mm Hg) were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 19 publications
(23 reference statements)
4
56
0
Order By: Relevance
“…After withdrawal, aliskiren plasma levels dropped within 24 h to nondetectable, whereas a delayed decline over several days was found in the heart and kidney. Interestingly, this contrasts with plasma half-life of aliskiren in humans (ϳ30 -40 h after multiple dosing) (15), which was used to explain sustained reduced blood pressure after a missed dose and may counteract adverse effects due to imperfect adherence (5,31). Interspecies variation of the pharmacokinetic entities of aliskiren thus need further evaluation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…After withdrawal, aliskiren plasma levels dropped within 24 h to nondetectable, whereas a delayed decline over several days was found in the heart and kidney. Interestingly, this contrasts with plasma half-life of aliskiren in humans (ϳ30 -40 h after multiple dosing) (15), which was used to explain sustained reduced blood pressure after a missed dose and may counteract adverse effects due to imperfect adherence (5,31). Interspecies variation of the pharmacokinetic entities of aliskiren thus need further evaluation.…”
Section: Discussionmentioning
confidence: 90%
“…Emerging evidence indicates sustained effects of aliskiren beyond withdrawal (31,35). Besides its long plasma half-life in humans, speculations about any putative renal accumulation of aliskiren were held to explain this phenomenon (10).…”
Section: /6 Nephrectomy; Renal Impairmentmentioning
confidence: 99%
“…Of 27 aliskiren clinical trials that have assessed BP changes in patients with hypertension as a primary end point, 8 met the study inclusion criteria and were evaluated in the meta-analysis. [11][12][13][14][15][16][17][18] Study details are shown in Table 1. PRA was measured in only a subset of patients in studies 3 to 8.…”
Section: Methodsmentioning
confidence: 99%
“…Although relatively poorly absorbed from the gastrointestinal tract, aliskiren is quite potent and its pharmacodynamic half-life markedly exceeds 24 hours [Palatini et al 2010]. This might carry with it potential importance in individuals more likely to miss drug doses, a characteristic that is more frequent in minorities.…”
Section: Other Factorsmentioning
confidence: 99%